Hyperthyroidism in pregnancy - Franco-Herrera, Daniela (2018)
The association of hyperthyroidism and pregnancy is rare. Its importance resides in the prognosis of mother and fetus. The recognition of thyroid alterations during pregnancy differs from the general population; in this special group, it is necessary to correlate diagnostic tests and normal physiological changes. The main cause of hyperthyroidism is Graves disease, with its autoimmune component. Transient gestational thyrotoxicosis becomes important during pregnancy and is critical in the differential diagnosis, especially during the first trimester. Management of hyperthyroidism during pregnancy has special implications; first-line therapies are contraindicated, and antithyroid drugs become relevant. No therapy is completely safe during pregnancy; possible adverse effects and mother and fetus implications must be evaluated. In this review, we want to consider the physiological changes in thyroid function during pregnancy. Also, we want to point out the best actions for the proper recognition, diagnosis and management of hyperthyroidism during pregnancy, in order to reduce maternal and fetal morbidity and mortality. A review of the literature was performed in PubMed and Science Direct using MeSH words and connectors. We included the most relevant articles published by scientific societies in the last 20 years on the diagnosis and management of hyperthyroidism during pregnancy.